A time-series meta-transcriptomic analysis reveals the seasonal, host, and gender structure of mosquito viromes. Issue 1 (2nd February 2022) - Feng, Yun; Gou, Qin-yu; Yang, Wei-hong; Wu, Wei-chen; Wang, Juan; Holmes, Edward C; Liang, Guodong; Shi, Mang
Abstract: Although metagenomic sequencing has revealed high numbers of viruses in mosquitoes sampled globally, our understanding of how their diversity and abundance varies in time and space as well as by host species and gender remains unclear. To address this, we collected 23, 109 mosquitoes over the course of 12 months from a bat-dwelling cave and a nearby village in Yunnan province, China. These samples were organized by mosquito species, mosquito gender, and sampling time for meta-transcriptomic sequencing. A total of 162 eukaryotic virus species were identified, of which 101 were novel, including representatives of seventeen RNA virus multi-family supergroups and four species of DNA virus from the families Parvoviridae, Circoviridae, and Nudiviridae . In addition, two known vector-borne viruses—Japanese encephalitis virus and Banna virus—were found. Analyses of the entire virome revealed strikingly different viral compositions and abundance levels in warmer compared to colder months, a strong host structure at the level of mosquito species, and no substantial differences between those viruses harbored by male and female mosquitoes. At the scale of individual viruses, some were found to be ubiquitous throughout the year and across four mosquito species, while most of the other viruses were season and/or host specific. Collectively, this study reveals the diversity, dynamics, and evolution of the mosquito virome at a single location and sheds new lights on the ecology of these important vector animals.